Carbon dioxide emission standards for US power plants: An efficiency analysis perspective - Benjamin Hampf; Kenneth Løvold Rødseth (Technische Universität Darmstadt, Department of Law and Economics, 2014)
On June 25, 2013, President Obama announced his plan to introduce carbon dioxide emission standards for electricity generation. This paper proposes an efficiency analysis approach that addresses which mission rates (and standards) would be feasible if the existing generating units adopt best practices. A new efficiency measure is introduced and further decomposed to identify different sources' contributions to emission rate improvements. Estimating two Data Envelopment Analysis (DEA) models - the well-known joint production model and the new materials balance model - on a dataset consisting of 160 bituminous-fired generating units, we find that the average generating unit's electricity-to-carbon dioxide ratio is 15.3 percent below the corresponding best-practice ratio. Further examinations reveal that this discrepancy can largely be attributed to non-discretionary factors and not to managerial inefficiency. Moreover, even if the best practice ratios could be implemented, the generating units would not be able to comply with the EPA's recently proposed carbon dioxide standard.
Keywords: Q53; Q48; D24; 330; Emission standards; Carbon dioxide emissions; Materials balance condition; Electricity generation; Weak G-disposability; Data Envelopment Analysis